Determination of velocity and direction of ground water flow in san andres island by means of radiotracers (1975)
The injection of radiotracers in 10 boreholes in San Andres island allowed the determination of direction and velocity of ground water flow. The basis of the technique relates to the application of a relationship existing between the observed concentration decrease of a radio tracer solution introduced into a borehole and the velocity of the undisturbed ground water flow in the aquifer.  The change of the tracer's position indicates the direction of flow. Satisfactory results show that techniques described herein are cheap, simple and rapid methods' for the determination of important hydrogeological characteristics.